2013
DOI: 10.1177/0972652713512916
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Board Structure in Microfinance Institutions: Evidence from East Africa

Abstract: This study investigates the association between the unique characteristics of microfinance institutions and board structure. The agency and resource dependence theories provided theoretical guidance for this study. Using a panel dataset of 63 microfinance institutions in East Africa, we found that the presence of regulations and international influence is associated with larger boards, while the presence of founders is associated with small boards and less board independence. There is a higher level of board g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…Several researchers have responded to the call for more knowledge on the governance of MFIs. The core interest of these studies has been the effectiveness of the link between board characteristics and MFI performance-such as board structure (Mori et al, 2013), board diversity (Hartarska, 2005;Hartarska & Mersland, 2012), board composition, CEO duality, and board size (Mersland & Strøm, 2009). These articles mostly look at how boards are structured and formed in terms of who sit on those boards, how large are the boards and how independent they are.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have responded to the call for more knowledge on the governance of MFIs. The core interest of these studies has been the effectiveness of the link between board characteristics and MFI performance-such as board structure (Mori et al, 2013), board diversity (Hartarska, 2005;Hartarska & Mersland, 2012), board composition, CEO duality, and board size (Mersland & Strøm, 2009). These articles mostly look at how boards are structured and formed in terms of who sit on those boards, how large are the boards and how independent they are.…”
Section: Introductionmentioning
confidence: 99%
“…Certain microfinance services' suppliers in Uganda including; PRIDE, FINCA and Centenary Rural Development Bank are near to financial sustainability or have now surpassed it (Wright et al, 1998). Microfinance amenities contribute to reduced customer vulnerability to economic perils, contributes to firming linkages of clients and their families to the agricultural sector, rejuvenates economic well-being of areas previously under conflict and enables clients to acquire valued skills, (Hoxhaj, 2010;Strand, Kjøllesdal, & Sitter, 2010;Mori & Randoy, 2011). Sustainability in development and promotion of MFIs has been viewed as a promising development policy able to address market failures in formal banking systems (Basu, 2005).…”
Section: Other Relevant Scientific Issues To the Studymentioning
confidence: 99%
“…For instance, in their study, Mori et al (2013) investigated the individual and firm-level determinants of the MFI corporate board. Their study revealed that some corporate governance characteristics play a significant role in shaping the board structure of an MFI.…”
Section: Antecedents and Consequences Of Governancementioning
confidence: 99%